2001
DOI: 10.1149/1.1397774
|View full text |Cite
|
Sign up to set email alerts
|

Nonflammable Trimethyl Phosphate Solvent-Containing Electrolytes for Lithium-Ion Batteries: II. The Use of an Amorphous Carbon Anode

Abstract: In order to improve the cycling performance of lithium-ion batteries with nonflammable trimethyl phosphate ͑TMP͒-based electrolytes, amorphous carbon ͑AC͒ was used as the anode material. It was found that the reduction decomposition of TMP solvent, which occurred without limit on a natural graphite anode and concomitantly generated a large amount of methane (CH 4 ) and ethylene (C 2 H 4 ) gases, was considerably suppressed on amorphous carbon anode. This improvement was attributed to the disordered structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 20 publications
0
76
0
1
Order By: Relevance
“…For instance, althoughT MP and DMMP are highly efficient FRs, they do not form as table SEI layer,w hich then has ad etrimentali mpact on the coulombic efficiency,a nd thus, the cycling stability. [138,143] Hence, the design of additives with high FR characteristics needs to comply with the formationo farobust SEI layer,a nd thereby, electrochemical compatibility.I nt he pursuit of alleviating the trade-off between flammability and cell performance, severalm ethods are effective, includinga ni ncrease in the alkyl chain length, [140] the development of fluorinated organophosphorus compounds, [144][145][146] the partial replacemento fa lkyl groups by aryl(phenyl) groups, [147,148] and the utilization of cyclic phosphates. [149] Fluorinated phosphates,f or instance, possess ac ouple of attractive features www.chemsuschem.org compared with non-fluorinated ones, showing, amongo ther things, ah ighly synergistic effect of both fluorine and phosphorusa nd enablingt he formationo fastable SEI on graphite anodes.…”
Section: Flame-retardant Additivesmentioning
confidence: 99%
“…For instance, althoughT MP and DMMP are highly efficient FRs, they do not form as table SEI layer,w hich then has ad etrimentali mpact on the coulombic efficiency,a nd thus, the cycling stability. [138,143] Hence, the design of additives with high FR characteristics needs to comply with the formationo farobust SEI layer,a nd thereby, electrochemical compatibility.I nt he pursuit of alleviating the trade-off between flammability and cell performance, severalm ethods are effective, includinga ni ncrease in the alkyl chain length, [140] the development of fluorinated organophosphorus compounds, [144][145][146] the partial replacemento fa lkyl groups by aryl(phenyl) groups, [147,148] and the utilization of cyclic phosphates. [149] Fluorinated phosphates,f or instance, possess ac ouple of attractive features www.chemsuschem.org compared with non-fluorinated ones, showing, amongo ther things, ah ighly synergistic effect of both fluorine and phosphorusa nd enablingt he formationo fastable SEI on graphite anodes.…”
Section: Flame-retardant Additivesmentioning
confidence: 99%
“…114 It was found that the reduction decomposition of TMP solvent, which occurred without limit on a natural graphite anode and concomitantly generated a large amount of methane (CH 4 ) and ethylene (C 2 H 4 ) gases, was considerably suppressed on an amorphous carbon anode. The charge/discharge data and cyclic voltammetry indicated the formation of a highly stable and passivating surface film on the carbon surface at a potential near 1 V. In terms of safety, the ionic-liquid-based inorganic electrolyteLiBF4 in 1-ethyl-3-methylimidazolium tetra fluoroborate (EMI-BF4) -is one alternative because of its higher boiling point than that of LiPF 6 in EC/DEC and non-flammability.…”
Section: Carbonaceous Electrodesmentioning
confidence: 99%
“…One of the most immediate strategies to address the thermal safety of electrolytes is to lower the electrolyte inflammability by using flame retardants as additives or cosolvents [3][4][5][6][7][8][9][10][11][12][13][14]. Among the variety of flame retardant additives, organophosphates are commonly applied, due to their low viscosity and high solubility, such as trimethyl phosphate (TMP) [3][4][5], triethyl phosphate (TEP) [6], dimethyl methylphosphonate (DMMP) [7,11,15], diethyl ethylphosphonate (DEEP) [8], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Among the variety of flame retardant additives, organophosphates are commonly applied, due to their low viscosity and high solubility, such as trimethyl phosphate (TMP) [3][4][5], triethyl phosphate (TEP) [6], dimethyl methylphosphonate (DMMP) [7,11,15], diethyl ethylphosphonate (DEEP) [8], and so on. However, organophosphates have the drawbacks of lower flame retardant efficiency and poor electrochemical compatibility with electrode materials.…”
Section: Introductionmentioning
confidence: 99%